2012
DOI: 10.3390/ijms13044433
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Transient Receptor Potential Vanilloid (TRPV) Channels in Different Passages of Articular Chondrocytes

Abstract: Ion channels play important roles in chondrocyte mechanotransduction. The transient receptor potential vanilloid (TRPV) subfamily of ion channels consists of six members. TRPV1-4 are temperature sensitive calcium-permeable, relatively non-selective cation channels whereas TRPV5 and TRPV6 show high selectivity for calcium over other cations. In this study we investigated the effect of time in culture and passage number on the expression of TRPV4, TRPV5 and TRPV6 in articular chondrocytes isolated from equine me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…Previous studies have observed [Ca 2+ ] i signaling in response to mechanical loading (38,39); interestingly, these studies detected [Ca 2+ ] i signaling in chondrocyte-laden constructs without substantial preculture (<72 h), although chondrocytes synthesize small amounts of pericellular proteoglycans even within 2 d of culture in agarose (29) that could contribute to mechanically induced [Ca 2+ ] i signaling. Thus, the effects of loading with and without preculture, observed in this study as well as in previous studies, may be due to differences in the characteristics of the [Ca 2+ ] i signal with preculture, or perhaps other environmental and cellular factors that change over time (24,26,28,40). Although chondrocyte [Ca 2+ ] i signaling exhibits a high sensitivity to variations in osmolarity or volume (41)(42)(43)(44), there is little or no sensitivity to physiologic levels of other physical stimuli, such as direct membrane stretch, suggesting that membrane connections to the pericellular matrix and/or intracellular cytoskeleton are important for the generation and transduction of [Ca 2+ ] i transients.…”
Section: Camentioning
confidence: 78%
“…Previous studies have observed [Ca 2+ ] i signaling in response to mechanical loading (38,39); interestingly, these studies detected [Ca 2+ ] i signaling in chondrocyte-laden constructs without substantial preculture (<72 h), although chondrocytes synthesize small amounts of pericellular proteoglycans even within 2 d of culture in agarose (29) that could contribute to mechanically induced [Ca 2+ ] i signaling. Thus, the effects of loading with and without preculture, observed in this study as well as in previous studies, may be due to differences in the characteristics of the [Ca 2+ ] i signal with preculture, or perhaps other environmental and cellular factors that change over time (24,26,28,40). Although chondrocyte [Ca 2+ ] i signaling exhibits a high sensitivity to variations in osmolarity or volume (41)(42)(43)(44), there is little or no sensitivity to physiologic levels of other physical stimuli, such as direct membrane stretch, suggesting that membrane connections to the pericellular matrix and/or intracellular cytoskeleton are important for the generation and transduction of [Ca 2+ ] i transients.…”
Section: Camentioning
confidence: 78%
“…In nonexcitable cells such as chondrocytes, membrane hyperpolarization facilitates Ca 21 entry through nonselective cation channels (Gavenis et al, 2009;Funabashi et al, 2010b;Hdud et al, 2012). Blockage of Cl 2 channels by DIDS caused a significant hyperpolarization followed by an increase in [Ca 21 ] i .…”
Section: Discussionmentioning
confidence: 99%
“…The expression level of the BK Ca channel in EACs following exposure to hypo-osmotic, mild hypo-osmotic, and hyperosmotic stresses was monitored at different time points. Western blotting using a BK Ca channel-specific antibody was used to examine the effect of osmotic stress on BK Ca channel expression, as previously described (16). There were no significant changes in BK Ca channel expression following hypo-osmotic and mild hypo-osmotic stress after 90 min and 3 h, whereas 6 h of incubation under hypo-osmotic conditions induced a significant (1.5-fold) increase in BK Ca channel expression (P Ͻ 0.01; Fig.…”
Section: Effect Of Osmotic Stress On Expression Of Ion Channelsmentioning
confidence: 99%
“…A medium osmolarity of 380 mosM was used as the control condition. Western blotting using a TRPV4 channel-specific antibody, as described previously (16), was used to explore TRPV4 channel expression following hypoosmotic, mild hypo-osmotic, and hyperosmotic stress. Exposure of chondrocytes to hypo-osmotic stress for 6 h (P Ͻ 0.01), 3 h (P Ͻ 0.001), and 90 min (P Ͻ 0.001) increased TRPV4 channel expression by Ͼ1.5-fold (Fig.…”
Section: Effect Of Osmotic Stress On Expression Of Ion Channelsmentioning
confidence: 99%
See 1 more Smart Citation